2020
DOI: 10.9734/ajmah/2020/v18i330193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pearl Millet on Glycaemic Control and Lipid Profile in Streptozocin Induced Diabetic Wistar Rat Model

Abstract: Aims: This study was designed to investigate the effect of Pear millet on glycaemic control and lipid profile in streptozocin diabetic rat model. Methodology: Forty healthy mature male rats were used in this study. The rats divided into 4 groups, ten rats in each and group (A) and (B) normal control rats while group (C) and (D) considered as diabetic rats. Diabetes induced by intraperitoneal injection of 40 mg/kg streptozocin and confirmed by high blood glucose level which considered day 0. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Hence, there were significant differences (P<0.05) in the fasting blo od glucose (FBG) levels across all the groups except three days mentioned above. Sukar et al (2020) reported that there was significant (P<0.05) reductions in blood glucose, LDL levels and significant (P<0.05) elevation in adiponectin and HDL levels were detected in rats fed with pearl millet which is in support to the result of this study. This study upheld the study by Park et al (2008) established that there is an effect on the glycemic response of diabetic mice.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Hence, there were significant differences (P<0.05) in the fasting blo od glucose (FBG) levels across all the groups except three days mentioned above. Sukar et al (2020) reported that there was significant (P<0.05) reductions in blood glucose, LDL levels and significant (P<0.05) elevation in adiponectin and HDL levels were detected in rats fed with pearl millet which is in support to the result of this study. This study upheld the study by Park et al (2008) established that there is an effect on the glycemic response of diabetic mice.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Sukar et al (2020) [ 54 ] showed substantial elevation of adiponectin associated with a vast decrease in blood glucose levels during the study periods. These findings imply that, feeding with the whole grain of pearl millet, a diet can play a significant role in restoring the plasma level of adiponectin to the physiological level.…”
Section: Pearl Millet and Diabetesmentioning
confidence: 99%
“…Vários benefícios para a saúde têm sido observados devido ao consumo dos milhetos, incluindo efeitos anti-inflamatórios e antioxidantes in vitro e em animais (CHANDRASEKARA; SHAHIDI, 2012;DIAS-MARTINS et al, 2018;THEODORO et al, 2021b); antidiabéticos in vitro e em humanos e em animais PEI et al, 2022;SUKAR et al, 2020); hipolipemiante em animais (ALZAHRANI et al, 2022;THAKUR et al, 2021;THAKUR;DHALIWAL, 2021); no controle das sensações de saciedade in vitro e em humanos (MONDAL et al, 2022;REN et al, 2018); redução de risco de obesidade e de distúrbios metabólicos em animais (ALZAHRANI et al, 2022;AMBATI;SUCHARITHA, 2019); e anticarcinogênicos in vitro e in silico (AGREGÁN et al, 2022;SAINI et al, 2021;LIU, 2015).…”
unclassified